1968
DOI: 10.2105/ajph.58.5.836
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of possible etiologic factors in multiple sclerosis.

Abstract: Using an epidemiologic approach, a test was made in Israel of the hypothesis that the peculiar geographic distribution of multiple sclerosis may be accounted for by an environmental factor correlated with latitude. The results are presented and compared with a previous survey conducted in 1963.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

1972
1972
2001
2001

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 14 publications
(3 reference statements)
1
18
1
3
Order By: Relevance
“…Similar results have been reported from surveys of NE Scot land [9], Oxford [68], Los Angeles and Seattle [69]. Studies in Winnipeg [30], Israel [70] and Northern Ireland [71] have failed to find this association. The study of United States army recruits by Beebe et al [72], is unique in hav ing prospective data on educational and occu pational level for cases with disease onset after army recruitment.…”
Section: Other Epidemiological Aspects Of M Ssupporting
confidence: 84%
“…Similar results have been reported from surveys of NE Scot land [9], Oxford [68], Los Angeles and Seattle [69]. Studies in Winnipeg [30], Israel [70] and Northern Ireland [71] have failed to find this association. The study of United States army recruits by Beebe et al [72], is unique in hav ing prospective data on educational and occu pational level for cases with disease onset after army recruitment.…”
Section: Other Epidemiological Aspects Of M Ssupporting
confidence: 84%
“…If well water is associated with MS, then logi cally farm/ranch residence should have been identified as a risk factor in studies which have examined urban versus rural residence as a variable. Except for this study and one in Northern Ireland, which found a defi ciency of cases in Belfast [24], studies have found an increased risk in urban areas [25] or observed no difference between urban and farm/ranch residence [11,19,[26][27][28]. Although use of well water would certainly be more common on farms/ranches, this study also included some patients and con trols from small towns/villages who used well water, so that these factors are not en tirely interdependent.…”
Section: Discussioncontrasting
confidence: 52%
“…The impact of early life residence seems less clear for migrants to Australia [33], However, the role of selection factors in determining who migrates and to where has rarely, if ever, been addressed. This is most strikingly evident in the study of Vietnamese migrants to France [34], A substantial increase in risk for M S appeared to occur in these migrants com pared to the risk characterizing the 'native' Vietnamese population.…”
Section: Ebers/sadovnickmentioning
confidence: 99%